2017
DOI: 10.1001/jamaneurol.2017.1200
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Motor Symptoms and Brain Metabolism in Early Huntington Disease

Abstract: IMPORTANCE Brain hypometabolism is associated with the clinical consequences of the degenerative process, but little is known about regional hypermetabolism, sometimes observed in the brain of patients with clinically manifest Huntington disease (HD). Studying the role of regional hypermetabolism is needed to better understand its interaction with the motor symptoms of the disease.OBJECTIVE To investigate the association between brain hypometabolism and hypermetabolism with motor scores of patients with early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
(81 reference statements)
2
19
0
Order By: Relevance
“…In fact, a recent study looking at PET imaging in AOHD found that the cerebellum seemed to be playing both pathologic and compensatory roles at the same time. 28…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study looking at PET imaging in AOHD found that the cerebellum seemed to be playing both pathologic and compensatory roles at the same time. 28…”
Section: Discussionmentioning
confidence: 99%
“…While somewhat overlooked in the past, the cerebellum has recently been described as both potentially pathologic, as well as compensatory in HD [49][50][51]. The cerebellum is often regarded as being 'spared' from neurodegeneration caused by HD.…”
Section: The Cerebellum Is Compensatory To the Abnormally Developed Smentioning
confidence: 99%
“…45,46 A recent study reports similar findings of striatal hypometabolism in combination with hypermetabolism in the cerebellum, thalamus, and occipital cortex. 47 Here, hypermetabolism in the cuneus and lingual gyrus was negatively correlated with hypokinetic motor scores. These findings suggest that a decrease in glucose metabolism might be linked to clinical disease onset, whereas an increase in glucose metabolism indicates a compensatory mechanism for neuronal loss and/or motor disturbances.…”
Section: Cerebral Metabolismmentioning
confidence: 79%
“…These findings suggest that a decrease in glucose metabolism might be linked to clinical disease onset, whereas an increase in glucose metabolism indicates a compensatory mechanism for neuronal loss and/or motor disturbances. 46,47 As neuronal loss is indirectly measured using functional MRI, the reduced brain activity in the occipital cortex of HD patients found in previous fMRI studies might indeed explain the hypermetabolism found in these PET studies.…”
Section: Cerebral Metabolismmentioning
confidence: 91%